Alcohol in Teenagers of Amritsar District: A KAP Study - Kaur, Navpreet; Chaudhary, R K; Gupta, Pankaj; Devgun, Priyanka; Khurana , Baljit Singh (Journal of Indian Academy of Forensic Medicine, 2015)
Today alcohol is widely available and aggressively promoted throughout society. And alcohol use continues to be regarded as normal part of growing up. Yet underage drinking is dangerous not only for the drinkers but also for society as evident by the number of alcohol involved motor vehicle crashes, homicides, suicides and other injuries. As children move from adolescence to young adulthood, they encounter dramatic physical, emotional and lifestyle changes. They are at the threshold of adolescence and ready to step into adult role. They follow their peers and mimic their parents ultimately forming their own opinions. Experimentation with new things and ideas is the new mantra for living their lives. For some teens thrill seeking might include experimenting with alcohol. An adolescent who expects drinking to be a pleasurable experience is more likely to drink than one who does not. In the present study we have tried to assess the knowledge, attitude and practices regarding alcohol in the students belonging to age group 17- 20years.